MODIFIKASI TECHNOLOGY ACCEPTANCE MODEL DALAM MENGUKUR ADOPSI CORE TAX ADMINISTRATION SYSTEM - Zahrah Salsabila Putri (2023)
This research is a quantitative study that aims to determine the factors that influence the adoption of the core tax administration system with the samples being tax officials at KPP Madya Batam, KPP Pratama Gorontalo and KPP Pratama Bekasi Barat. Sampling using purposive sampling method with a total sample of 166 tax officers. Testing the hypothesis in this study using LISREL 8.80 by looking at the t-value. The test results show that (1) there is no influence between self-efficacy and perceived usefulness, (2) there is a significant positive effect between self-efficacy and perceived ease of use, (3) there is no effect between complexity and perceived usefulness, (4) there is no influence between complexity and perceived ease of use, (5) there is a significant positive effect between perceived ease of use and perceived usefulness, (6) there is no effect between perceived usefulness and intention to use, and (7) there is no influence between perceived ease of use with intention to use.